(3GdefgLjI GdYdejI dEYGOI JQeje hUjGfI HYV GdebJfjGJ GdMLQjI SGHbI GdJQeje HGdeJMa GdeUQj HGdbGgQI (B/ s - (3EjeGf CMeO GdMfaj CMeOs; (3YHdI YHOGdSdGe YeQ (B: s; (3eMeO YHOGdgGOj eMeO (B: s ((3GdbGgQI (B: s (3EjeGf CMeO GdMfaj CMeO (B: s, 2017)
(3JfGhdJ GdQSGdI OQGSI ehGO GdJQeje GdSGHbI GdeSJNOeI ai KdGK ef GdBKGQ GdMLQjI ddMLQ GdLjQi h GdLjQGfjJ h GdMLQ GdQedi h OQGSI CMOK GdehGO GdJi jecf ESJNOGegG ai EYGOI JQeje gPg GdBKGQ GdJi JhGLOJ ai HjFI eNRf GdeJMa GdeUQi HGdbGgQI h JeJ OQGSI GdHjFI GdeNRfjI GdeJhGLO ajgG GdBKGQ deYQaI BKQ OQLGJ GdMQGQI h GdQWhHI h GdVhA Ydi Jda gPg GdBKGQ h ehGO GdJQeje HgG h Je QUO deXGgQ GdJda GdfGJLI Yf gPg GdYhGed cPdc Je OQGSI GdHjFI GdeNRfjI GdfehPLjI hGdJi jLH Cf JJhGLO HgG GdBKGQ h Je EYWGA fehPL dPdc HGdeJMa GdeUQi GdcHjQ h deYQaI fhGJL GdJda h BKGQgG Ydi GdBKGQ GdMLQjI Je Yed GdaMhU h GdJMGdjd HESJNOGe GdejcQhSchHGJ GdeNJdaI h JbfjGJ GdJcfhdhLjG GdMOjKI ai aMU h OQGSI GdBKGQ GdKdGKI h fhGJL GdJda HgG (B. (3Ke Je hVY aQhV YdGLjI dEMdGd GdehfGJ GdSGHbI h ehGO GdJOYje HGdBKGQ GdKdGKI h ESJHOGdgG HGdehGO GdSGHbI h Pdc HYO ELQGA YedjGJ GdJLQjH GdeNJdaI (B( (3ehfI LjQGfjJ (B{u(32013(B} (3ehfI MLQ LjQi (B) (3h dhGUb (B( (3ddMLQ GdQedi (B) (3h CYeOI JLejY ddCMLGQ (B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdJQeje s
(3UOQ GjVG cbQU eOeLs
Keywords: (3JOghQ s; (3JQeje SGHbs; (3YdGLs